It's in the mix: psychological distress differs between combinations of alexithymic facets - Alkan Härtwig, Elif; Crayen, Claudia; Heuser, Isabella; Eid, Michael (Frontiers in Psychology, 2014)
Alexithymia is a personality trait characterized by difficulties in identifying, describing, and communicating one’s emotions. The aim of the present study is to examine the usefulness of a typological approach considering the interaction between distinct alexithymic features within a population of high-alexithymic German adults (N=217). Latent profile analysis (LPA) was employed to test for possible underlying profiles. A 3-profile solution showed the best fit: The profiles can be described as (1) “low”: lower load on all facets of alexithymia, (2) “mixed”: specific problems on identifying emotions, and (3) “high”: higher load on all facets of alexithymia. Moreover, this study tested how these profiles differed in psychological distress. “Mixed” profile, with specific problems on identifying emotions showed the highest levels of psychological distress. The present study suggests the importance of a specific combination of alexithymic features, rather than total alexithymia scores, as a risk factor for psychological distress.